ChemInform Abstract: A Novel Method to Access Chiral Nonnatural 2, 4‐Disubstituted Pyrrolidines from Aldehydes and Nitroolefins Only with an α‐Substituent. Issue 38 (30th August 2013) - Zheng, Bo; Wang, Hui; Han, Yong; Liu, Changlu; Peng, Yungui
Abstract γ‐Nitro carbonyl products (III) are obtained in good yields and stereoselectivities via the organocatalytic asymmetric Michael addition of nitroolefins (II) with aldehydes (I).